2002
DOI: 10.1007/s005350200170
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection in hospital workers over a 5-year period: correlation with demographic and clinical parameters

Abstract: In this longitudinal study of workers in a large acute care hospital in Greece it was found that nursing staff had a significantly higher risk of infection compared with administrative and technical staff. Age was significantly positively related both to H. pylori infection and to seroconversion. The level of education was strongly related to the prevalence, but not to the incidence of H. pylori infection. The presence of infection over the time was associated with a higher percentage of heartburn, regurgitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…While H. pylori positivity rates were not measured in this study, it is interesting to note that higher education levels have been associated with lower rates of this infection among HCWs in other parts of the world, and this could explain this result. [17] The presence and relative frequency of two major dyspeptic symptom complexes in this study is revealing. While the previous literature describes most African patients as suffering from ulcerlike symptoms, in our study refluxlike symptoms were just as common, and just as likely to be rated as the major symptom.…”
Section: Discussionmentioning
confidence: 56%
“…While H. pylori positivity rates were not measured in this study, it is interesting to note that higher education levels have been associated with lower rates of this infection among HCWs in other parts of the world, and this could explain this result. [17] The presence and relative frequency of two major dyspeptic symptom complexes in this study is revealing. While the previous literature describes most African patients as suffering from ulcerlike symptoms, in our study refluxlike symptoms were just as common, and just as likely to be rated as the major symptom.…”
Section: Discussionmentioning
confidence: 56%
“…[63] investigated whether medical or non-medical staff in a large acute care hospital was at increased risk of acquiring H. pylori infection over a 5-year period. They observed an annual seroconversion rate of 4.95% and found that nursing staff had a significantly higher risk of infection compared with administrative and technical staff.…”
Section: Modes Of Transmissionmentioning
confidence: 99%
“…Conflicting data have been reported on occupational risk in health personnel for H. pylori infection 7,18,19. One longitudinal study in Greece found that nurses had a significantly higher risk of infection compared with doctors and medical controls 19.…”
Section: Discussionmentioning
confidence: 99%
“…One longitudinal study in Greece found that nurses had a significantly higher risk of infection compared with doctors and medical controls 19. Peters et al7 also reported the occupational risk of H. pylori infection among gastroenterologists and their assistants.…”
Section: Discussionmentioning
confidence: 99%